WASIAT WAJIBAH DI TINJAU DARI HUKUM ISLAM DAN HUKUM POSITIF (BW) - Bachtiar, Mochamad Alfan; Wahjoehono, Dipo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
In Islamic Law, adopted children are different from biological children in the division of inheritance. The biological child is entitled to an inheritance, while the adopted child is not an heir, so he not is entitled to an inheritance. However, he is entitled to a maximum of 1/3 of the inheritance through a mandatory will. This becomes a question, what happens when parents want to give inheritance to their adopted children. This research discusses the mandatory will for adopted children to get inheritance by analyzing the Palembang Religious Court Decision No. 35/Pdt.G/2018/PTA. This research is a type of literature research. The nature of his research is descriptively analytical, using a qualitative approach. The primary data source used is the Palembang Religious Court Decision No. 35/Pdt.G/2018/PTA. Plg while secondary data in the form of books and journal articles. The collected data is then organized, edited and analyzed through deductive analogies. The results of the study yielded two conclusions. First, in Court Decision No. 35/Pdt.G/2018/PTA. PLg, the judge granted inheritance rights to adopted children through compulsory wills under article 209 of the Compilation of Islamic Law and the benefit of adopted children. Because both parents have died, the adopted child gets 1/6 of each adoptive parent so that it does not exceed 1/3 of the inheritance. Second, from the Islamic law perspective, Court Decision No. 35/Pdt.G/2018/PTA. PLg on the will of the obligatory has been in accordance with Islamic law